On their own: towards an analysis of sealers' sites on Heard Island - AA McGowan (Papers and Proceedings of the Royal Society of Tasmania, 2000)
Heard Island is possibly the remotest speck of land on the Earth. It was only in the 1850's that the human race finally reached this most isolated of places. For the next 30 years gangs of hunters established themselves on the isolated beaches of Heard Island to slaughter the wildlife for their oil and furs and ship the products to markets half-way around the globe. The material culture remains of these enterprises survive on the beaches, comprising the remnants of the seal-hunters' camps and their processing sites. These sites provide evidence of 19th century sealing technology and the diverse ethnicity and cultural composition of the sealing gangs. Remains of sealers' camps are found on many of the beaches around Heard Island but are now extremely threatened by coastal erosion. Many of these sites include tryworks situated on raised stone platforms, a form of sealing architecture thought to be unique to Heard Island.